Workload Analysis Using the NASA-TLX Method on Mechanics at PT Statika Mitrasarana Padang City - Joni, Rahmi Rahmahwati; Milana, Milana; Fernandez, Donny; Saputra, Hendra Dani (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
Companies that own heavy equipment require regular maintenance. The amount of workload received by mechanic in the repair and maintenance section of heavy equipment units causes them to experience physical fatigue and frustration due to the workload and working hours being conducted outside of normal working hours. This study aims to determine the workload of mechanic at PT. Statika Mitrasarana. Data collection was carried out through direct observation of the mechanic, distribution of questionnaires, and interviews regarding the workload. The analysis of workload was conducted using the National Aeronautics and Space Administration Task Load Index (NASA TLX) method. From the results of the mechanic workload, an overall average of 83.6 was obtained. The highest workload has an average of 92.66 and the lowest 65.33. On the most dominant indicator of workload the physical demands have an average of 348. The measurement findings can help management consider additional steps, such as reducing and redistributing the mechanic workload.